1990
DOI: 10.1073/pnas.87.7.2506
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities of some tryptophan metabolites: possible implication for inflammatory diseases.

Abstract: The antioxidant properties of tryptophan and some of its oxidative metabolites were examined by measuring how efficiently they inhibited peroxyl radical-mediated oxidation of phosphatidyicholine liposomes and B-phycoerythrin.Low micromolar concentrations of 5-hydroxytryptophan, 3-hydroxykynurenine, xanthurenic acid, or 3-hydroxyanthranilic acid, but not their corresponding nonhydroxylated metabolic precursors, scavenged peroxyl radicals with high efficiency. In particular, 3-hydroxykynurenine and 3-hydroxyanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
183
2
3

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(200 citation statements)
references
References 45 publications
12
183
2
3
Order By: Relevance
“…However, specifically in macrophages and microglia, IFN-γ additionally induces the production of the metabolite 3-hydroxyanthranilic acid (3-HAA), a powerful antioxidant (34). Because 3-HAA is a robust free-radical scavenger (17), it was previously proposed that induction of this pathway by IFN-γ may represent a localized, extracellular antioxidant defense to protect host tissue from inadvertent oxidative damage that could occur during inflammatory conditions. This concept is in agreement with our studies, in which we found that the absence of IFN-γ signaling during EAE resulted in significantly enhanced lipid peroxidation products, as compared with WT mice, and corresponded to a more severe disease course that proceeded to a chronic inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, specifically in macrophages and microglia, IFN-γ additionally induces the production of the metabolite 3-hydroxyanthranilic acid (3-HAA), a powerful antioxidant (34). Because 3-HAA is a robust free-radical scavenger (17), it was previously proposed that induction of this pathway by IFN-γ may represent a localized, extracellular antioxidant defense to protect host tissue from inadvertent oxidative damage that could occur during inflammatory conditions. This concept is in agreement with our studies, in which we found that the absence of IFN-γ signaling during EAE resulted in significantly enhanced lipid peroxidation products, as compared with WT mice, and corresponded to a more severe disease course that proceeded to a chronic inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
“…Our results thus far strongly indicated a role for IFN-γ in limiting disease in EAE via modulating myelin Ag uptake and the removal of free myelin Ag by CNS APCs. It has been suggested previously that IFN-γ potentially could limit tissue damage during inflammation by limiting oxidative processes such as peroxidation of lipids (17). Myelin is lipid-rich; thus it was conceivable that peroxidation of lipids and/or proteins could be increased in the CNS of animals with disrupted IFN-γ signaling during EAE, in particular during the chronic phase of disease.…”
Section: Eae Severity Is Decreased Under Conditions Of Limited Availamentioning
confidence: 99%
See 1 more Smart Citation
“…Localized depletion of tryptophan in vivo has also been implicated in the immune evasion of certain tumors (9,10). Indoleamine 2,3-dioxygenase (IDO), the enzyme that regulates the rate-limiting step involved in the catabolism of tryptophan to kyneurenine, is also involved in the control of microbial infections (11)(12)(13)(14) and has been shown to have antioxidant properties (15)(16)(17). Pregnancy maintenance has also been associated with tryptophan catabolism by preventing the proliferation of maternal T-cells in response to tissues of the fetus expressing HLA alleles of the father (18).…”
mentioning
confidence: 99%
“…Finally, IDO induction during immune activation may protect cells from oxidative damage (87) . Indeed, 3-hydroxyanthranilic acid and 3-hydroxykynurenine, produced from tryptophan through the IDO-kynurenine pathway, have antioxidant properties (88) . This suggests that dietary tryptophan could influence the inflammatory response and the animal health.…”
Section: Control Of Inflammatory Response: Tryptophanmentioning
confidence: 99%